The Effect of Regional Original Income, Balancing Funds on Economic Growth and Their Impact on Poverty in Makassar City - Kamidin, Muh Ardiansyah M; Nujum, Syamsu; Mapparenta (Jurnal Economic Resource, 2024)
This study examines the influence of Regional Original Revenue and Balancing Funds on Economic Growth as mediating variables affecting Poverty. Using 2012–2022 secondary data from Bapenda and BPS Makassar City, the analysis employs Structural Equation Modeling (SEM). Results show Regional Original Revenue significantly impacts Economic Growth, while Balancing Funds do not. Both have a positive but insignificant effect on Poverty, whereas Economic Growth significantly influences Poverty. Indirectly, Regional Original Revenue and Balancing Funds via Economic Growth reduce Poverty significantly. The study recommends focusing on Regional Original Revenue management and allocating Balancing Funds for public initiatives to sustainably reduce Poverty.